FLOOD MODELING AND ECONOMIC IMPACT ON FLOOD-PRONE RESIDENTIAL AREAS IN THE CILOSEH RIVER BASIN, TASIKMALAYA - Prakoso, Wahyu Gendam; Irawan, Pengki; Setiawan, Junaedi; Rahmawati, Siti (International Journal of Civil Engineering and Infrastructure, 2025)
The Ciloseh River in Tasikmalaya City, West Java, spanning approximately 26.6 km with a 7,803-hectare catchment area, faces increasing flood vulnerability driven by rapid urban expansion and land-use conversion along its banks. This study systematically characterizes the river's floodplain morphology and quantifies potential economic losses from flooding across various return periods (2- to 50-year events). A comprehensive morphometric analysis of the watershed was conducted using Geographic Information Systems (GIS) to derive critical hydrological parameters. Flood discharge estimations were performed using the Synthetic Unit Hydrograph Gamma-I method. Hydrological data, augmented by field surveys, informed the development of a robust one-dimensional hydraulic model utilizing HEC-RAS software. The generated hydraulic model outputs were then integrated with high-resolution basemaps to produce detailed flood inundation maps. Economic loss assessments were rigorously performed following the ECLAC methodology, quantifying direct damages to infrastructure and residential properties. The analysis reveals significant flood inundation across all simulated return periods, with the 50-year event (Q50 = 473 m³/s) leading to a substantial inundated area of 46,151 m², affecting 244 residential units, and incurring estimated economic losses of IDR 3,188,421,996 (approximately USD 200,000). These findings provide essential data for developing sustainable flood mitigation strategies, informing urban planning, and guiding resilient infrastructure design in rapidly developing riverine environments. Keywords: Flood risk assessment, Hydraulic modeling, HEC-RAS, GIS, Economic impact, Urban hydrology, River engineering